Програмна система для візуалізації молекулярної хімії - Люліна, К. П. (ХНУРЕ, 2020)
Nowadays the problem of learning Chemistry and its main regularities among students has been risen due to the misunderstanding how the atoms are structured and how they react. The visualization of the chemical reaction can help to understand what happens with the atoms’ structure and what makes them react.